Strategi Guru Dalam Mengembangkan Image Building di Madrasah Aliyah Al-Islam Joresan Mlarak Ponorogo - Noris Aniqotul Azizah; Afif Syaiful Mahmudin (Moral : Jurnal kajian Pendidikan Islam, 2024)
This research was motivated by researchers' anxiety regarding the reduced attention of teachers to the importance of developing image building in Islamic schools. Image building or image formation, especially in educational institutions, plays an important role in building a school's reputation and increasing public trust and participation. However, the phenomenon observed by researchers shows that many teachers at Madrasah Aliyah pay little attention to this aspect, which can have an impact on public perception of the quality of the education provided. Therefore, this research aims to further explore teacher strategies in developing image building at Madrasah Aliyah Al-Islam Joresan Mlarak Ponorogo. The type of research used is qualitative field study using interview and observation data collection methods. The results of this research found that teachers' strategies in developing image building at Madrasah Aliyah Al-Islam Joresan include using the principle "al-muhafadhotu 'ala qodimis sholih wal akhdzu bil jadidil ashlah" which means "maintaining (maintaining) old values ​​or teachings good and adopt new and better values ​​or teachings," and empowering the environmental community at Madrasah Aliyah Al-Islam through teacher direction by the school principal.